(untitled) (Ameghiniana, 2013)
The brachiopods from the "Formación Quebrada larga" of the Quebrada Larga, province San Juan, Argentina is herein described. The presence of Heteralosia cornelliana (derby ) is reported for the first time in Argentina, and the identity of Buxtonia riojana (Leanza ) is discused. The gastropods, brachiopods and plant remains present in this formation can be refered to the Upper Carboniferous.